Late Pleistocene Red Sea Mollusca: 1. Polyplacophora - Dell’angelo, Bruno; Landau, Bernard M.; Sosso, Maurizio; Taviani, Marco (Zootaxa, 2020)
This study describes the chiton fauna (Mollusca, Polyplacophora) from the marine Pleistocene coral reef deposits bordering the Red Sea coast and dating to the last interglacial epoch (Marine Isotopic Substage 5e, MIS5e). Twenty-one species were identified, of which only three were previously known from the Pleistocene of the Red Sea (Lucilina sueziensis, Acanthopleura vaillantii and Acanthochitona penicillata). Eight are recorded as fossil for the first time. Six are described as new (Lucilina confusa n. sp., L. aqabaensis n. sp., L. aegyptiaca n. sp., L. colantonii n. sp., “Onithochiton” vandingeneni” n. sp., and Acanthochitona interglacialis n. sp.) and two are assigned at generic level (Callochiton sp. and Craspedochiton sp.). Four of these new species (Lucilina confusa n. sp., L. aegyptiaca n. sp., L. colantonii n. sp. and “Onithochiton” vandingeneni n. sp.) are still living in the Red Sea, bringing to 28 the number of extant species known from the Red Sea. These Pleistocene Red Sea assemblages represent the most diverse chiton fauna yet reported from any interglacial deposit worldwide.